DEVELOPMENT OF LAW OF SHARIA BANKING ON NATIONAL LEGAL DEVELOPMENT - Haidan, Haidan (Journal of Islamicate Studies, 2019)
This article will discuss the development of Islamic banking law in Indonesia. Through the literature survey, this article found that the development of Islamic banking law in Indonesia had begun since 1983 with the issuance of the December 1983 package which contained a number of regulations in the banking sector. One of them is a regulation that allows banks to provide loans with interest of 0% or zero interest. The growth was followed by a series of policies in the banking sector by the Minister of Finance at that time as contained in the October 1988 Package. The package was essentially banking deregulation which provided convenience for the establishment of new banks, so that the banking industry at that time experienced very rapid growth. Only in 1991, the mu'amalat Indonesia (BMI) bank become the only commercial bank that carried out business activities based on profit sharing principles. The introduction of banks based on the principle of profit sharing in positive law is through law Number 7 of 1992 concerning banking and government regulation No. 72 of 1992 concerning banks based on the principle of Profit Sharing. The empirical reality that shows that many conventional banks are unable to survive when the financial and monetary crisis hit, has encouraged the government to amend the law number 7 of 1992 set out in law number 10 of 1998. This law reinforces the existence of Islamic banking in Indonesia. The next step is the "purification stage" which is marked by the enactment of a law specifically regulating Islamic banking. On June 17, 2008, the Islamic banking law was passed, whose enactment in the State Gazette was conducted on July 16, 2008, namely Law No. 21 of 2008 concerning Islamic banking